Occupational Health Could be the New Normal Challenge in the Trade and Health Cycle: Keywords Analysis Between 1990 and 2020 - Sibel Kiran (Elsevier, 2021)
This brief report aims to establish the keyword content of studies on occupational health and safety-the key framework of the world of work in the trade and health domain. Data were collected from the SCOPUS database, focusing on articles on occupational health and safety and related keywords, with an emphasis on abstracts and titles. Data were analyzed and summarized based on keywords included from the MeSH database. There were 24,499 manuscripts in the domain and 1,346 (5.40%) occupational health-related keywords, including those that overlapped. The most frequently referenced occupational health-related keyword was "occupational health" (452 articles), followed by "occupational safety" (141 articles). There were fewer keywords on occupational health in the trade and health literature. As the world of work has been prioritized because of the recent new normal of work life since the COVID-19 pandemic, examining the focus of occupational health priorities within the global perspective is crucial.